2021
DOI: 10.3390/ijerph18126651
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Heated Tobacco Products and Adverse Health Effects, a Systematic Review

Abstract: Heated tobacco products (HTP) are a form of nicotine delivery intended to be an alternative to traditional cigarettes. HTP tobacco products are sold to consumers as a less harmful alternative to traditional cigarettes, both for users and bystanders. The actual impact of HTP on the health of users and its overall impact on public health is still not fully known. A systematic search of the literature was carried out to identify relevant studies published in English from 2015 to February 2021. The following datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 68 publications
0
74
0
6
Order By: Relevance
“…Heated tobacco products, other than e-cigarettes, have also been introduced into the market. Differences in the clinical risk markers for cardiovascular and respiratory diseases have been noted in a recent review, where users of heated tobacco products had a better biomarker profile compared to persistent smokers [28]. One study reported no short-term changes in tHcy in smokers using conventional cigarettes, randomized to smoking abstinence, menthol cigarettes, or menthol tobacco heating systems (n = 40, 42, and 78, respectively) [29].…”
Section: Discussionmentioning
confidence: 97%
“…Heated tobacco products, other than e-cigarettes, have also been introduced into the market. Differences in the clinical risk markers for cardiovascular and respiratory diseases have been noted in a recent review, where users of heated tobacco products had a better biomarker profile compared to persistent smokers [28]. One study reported no short-term changes in tHcy in smokers using conventional cigarettes, randomized to smoking abstinence, menthol cigarettes, or menthol tobacco heating systems (n = 40, 42, and 78, respectively) [29].…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, long term in vivo and clinical studies with adult smokers that have compared commercialised HTPs with combustible cigarette smoke exposure, have shown significant improvements in cardiovascular endpoints and related biomarkers upon switching from combustible cigarettes to HTPs ( Sakaguchi et al, 2014 ; Ogden et al, 2015 ; Smith et al, 2016 ; Schaller et al, 2016b ; Schaller et al, 2016a ; Pratte et al, 2017 ; Gale et al, 2019 ; Phillips et al, 2019 ; Shein and Jeschke, 2019 ; Tran et al, 2020 ; Wong et al, 2020 ). A recent systematic review of the health effects of HTP by Zynk et al (2021) reported favourable improvements in biomarkers related to cardiovascular and respiratory endpoints when comparing continued combustible cigarette smoking adult smokers who switched to using HTPs ( Znyk et al, 2021 ). Improvements in clinically relevant risk markers, especially cholesterol, sICAM-1, 8-epi-PGF2α, 11-DTX-B2, HDL and FEV1 have been observed when adult smokers switched away from combustible cigarettes to HTPs ( Zynk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Buchanan et al (2020) undertook a review of the clinical and pre-clinical studies conducted on e-cigarettes and concluded that the studies presented in their review "have shown that e-cigarettes can induce negative cardiovascular effects through various mechanisms such as oxidative stress, inflammation, DNA damage, arterial stiffness, and altered haemodynamics, and platelet activation." Furthermore, recent research suggests that HTP and EVP aerosols can affect the cardiovascular system, albeit it at exposures many magnitudes higher than combustible cigarette cardiotoxic exposures (Abouassali et al, 2021;Qasim et al, 2017;Znyk et al, 2021). The role of NGPs in relation to cardiovascular diseases is however, still a source of debate and controversy (NASEM 2018;Fried and Gardner, 2020;Tsai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISMA (preferred reporting items for systematic reviews and meta-analyses) was employed to guide this review [ 35 ].…”
Section: Methodsmentioning
confidence: 99%